Evaluating sea-level rise hazards on coastal archaeological sites, Trinity Bay, Texas. (2nd October 2021) - Elliott, Patrick; Williams, Harry
Abstract: This study uses the Sea Levels Affecting Marshes Model (SLAMM) to evaluate sea-level-rise hazards of erosion and inundation, on coastal archaeological sites in Trinity Bay, Texas. The SLAMM model was used to simulate the effects of a 1.5-m sea-level rise in the study area from 2006 to 2100. The model incorporated 177 archaeological sites, wetland categories, marsh accretion, wave erosion and surface elevation change. Modeling indicates that about 5, 500 hectares of marshlands will undergo large-scale conversion to unvegetated tidal flats or open water by 2100. Both accretion and inland migration will be insufficient to prevent large-scale losses of marshlands. Predicted erosion, on a site-by-site basis, is expected to affect 31% of archaeological sites by the end of the century. Predicted periods of inundation of archaeological sites were derived from ten years of tide data from a nearby tide gauge station, using NOAA's Inundation Analysis Tool. Approximately 55% of archaeological sites in the study area are predicted to be inundated at least half the time by the year 2100. Both inundation and erosion are predicted to have significant detrimental effects on archaeological sites in the study area. The study demonstrates that SLAMM is a useful tool for predicting potential future sea-level rise hazards on coastal cultural resources. Model outputs will be useful to coastal management agencies charged with evaluating impacts of sea-level rise and targeting high-risk sites for mitigation efforts.